An assessment of the health care needs of people aged 65 years and older in homes for the aged in Johannesburg - Zisis, Dafni (My University, 2014)
The purpose of this study was to explore the met and unmet needs of persons aged 65 years and older in three different homes for the aged in Johannesburg.